The exorcised. Demonic interference among the members of the Polish Charismatic religious communities (Przegląd Religioznawczy – The Religious Studies Review, 2022)
The dynamic expansion of the Neo-Pentecostal teachings across the world has given rise to the significant growth of interest in the question of demonic interference. John Wimber and Peter C. Wagner, who are believed to have been the most influential Neo-Pentecostal missionaries, spread the concept of spiritual warfare among their followers. This particular idea has become a substantial part of contemporary Christian Charismatic religious communities, also those located in Poland. What appears to be worth mentioning is that the members of the above-mentioned groups tend to perceive the activity of evil spirits as the main cause of their failures and emotional turmoil. The principal objective of this study is to investigate how the individuals who attend the Charismatic worship services in Poland conceptualize demonic interference and how this specific condition affects their daily functioning. Moreover, this research also refers to the similarities and differences between the ritual of exorcism in the Catholic Church and the deliverance ministry, which is typical of the so-called independent churches. Besides, the study attempts to put forward the concept of spiritual warfare in terms of its interpretation by the selected Charismatic religious communities. The analysis is based on individual in-depth interviews (IDI).